2012
DOI: 10.3389/fnhum.2012.00290
|View full text |Cite
|
Sign up to set email alerts
|

Multi-voxel pattern analysis in human hippocampal subfields

Abstract: A complete understanding of the hippocampus depends on elucidating the representations and computations that exist in its anatomically distinct subfields. High-resolution structural and functional MRI scanning is starting to permit insights into hippocampal subfields in humans. In parallel, such scanning has facilitated the use of multi-voxel pattern analysis (MVPA) to examine information present in the distributed pattern of activity across voxels. The aim of this study was to combine these two relatively new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 78 publications
(137 reference statements)
11
75
0
Order By: Relevance
“…The effects did not differ between art and room tasks (Ps > 0. 33). These control analyses demonstrate that the attentional state of the hippocampus-and CA2/CA3/DG in particularprovides uniquely meaningful information about memory formation.…”
Section: Predicting Memory From the Attentional State Of The Hippocampusmentioning
confidence: 75%
See 1 more Smart Citation
“…The effects did not differ between art and room tasks (Ps > 0. 33). These control analyses demonstrate that the attentional state of the hippocampus-and CA2/CA3/DG in particularprovides uniquely meaningful information about memory formation.…”
Section: Predicting Memory From the Attentional State Of The Hippocampusmentioning
confidence: 75%
“…We report results for these three subfield ROIs, as well as for a single hippocampal ROI collapsing across subfield labels. Moreover, motivated by computational theories and work with animal models, which highlight different roles for CA3 and DG in memory (32), as well as recent human neuroimaging studies that have examined these regions separately (33,34), we report supplemental exploratory analyses for separate CA2/3 and DG ROIs (Fig. S1).…”
Section: Significancementioning
confidence: 99%
“…Functional neuroimaging studies have likewise found group‐level HC activation during scene discrimination [Aly et al, 2013; Lee et al, 2008], scene construction/imagining [Zeidman et al, 2015], and working memory [Lee and Rudebeck, 2010b; Park et al, 2003]. Studies applying multivariate analysis techniques have also found evidence that the HC contains activation patterns that are sensitive to scene‐related information [Bonnici et al, 2012; Liang et al, 2013; but see Diana et al, 2008]. Overall, these extant data, when viewed alongside the large‐scale analysis of individual‐level data reported here, suggest that the HC should be considered a key region in the putative scene processing network [see also Kornblith et al, 2013; Kreiman et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…We combined high-resolution functional MRI (14) (fMRI) with an ultra-high resolution structural MRI scanning protocol that permitted the separate identification of CA1, CA3, dentate gyrus (DG), and subiculum (15,16). Stimuli were created by filming two brief action events against a green-screen background.…”
Section: Resultsmentioning
confidence: 99%
“…Manual segmentation of the hippocampal subfields was conducted using the ITK-SNAP software package (41) and a recently devised subfield segmentation protocol (15,16). It took on average 1 d to segment the subfields of one hippocampus.…”
Section: Methodsmentioning
confidence: 99%